STRATEGI PENGEMBANGAN WAKAF PRODUKTIF DALAM MENUMBUHKAN EKONOMI MASYARAKAT DI KOTA CILEGON BANTEN - Hendra Kholid; M. Dawud Arif Khan; M. Aqlus Salim (CV. Adiba Aisha Amira, 2023)
The results of this study indicate: First, mechanism waqf in implementing the Law no. 41 of 2004 as stipulated in article 43 paragraph 1 until 3, the concept of developing and managing waqf property is to be suitable principle sharia, to be developed and managed productively under its objectives, functions, and designations, and required guarantor. Second, Cilegon City applies its productive waqf management by renting out land, shophouses, photocopy machines, kiosks, boarding houses, and more. The reason is that the waqf assets owned by Cilegon City are mostly land and buildings. Third, a productive waqf has not brought any significant impacts on growing the community's economy in Cilegon City yet. because the bureaucracy or its management is not perfect and the waqf that is produced is not comprehensive. From previous research, the author agrees with what Annisa Fitria Utami et al. said in their scientific work entitled